Konstribusi Kepemimpinan Transformasional, Supervisi Akademik, Iklim Kerja, dan Budaya Organisasional Terhadap Prestasi Kerja Guru - L. Yuliani; A.A.G. Agung; I.M. Yudana (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to determine the magnitude of the variable contribution of transformational leadership, academic supervision, work climate, and organizational culture to teacher performance at SMK Negeri 1 Seririt. This type of research is ex post facto with a multiple linear regression analysis design. The population in this study was 61 people. The research sample for this study was 52 people. Collecting data using a questionnaire about the variables of transformational leadership, academic supervision, work climate, and organizational culture on teacher performance The results showed that: (1) there was a significant contribution of the principal's transformational leadership to teacher performance of 18.02%; (2) there was a significant contribution of academic supervision to teacher performance of 12.39%; (3) there was a significant contribution of work climate to teacher performance of 14.22%; (4) there was a significant contribution of organizational culture to teacher performance of 7.45%; and (5) there was a significant contribution of transformational leadership, academic supervision, work climate, and organizational culture together to teacher performance of 52.08%.